Measured Stark widths and shifts in the O IV spectrum - Đeniže Stevan (Serbian Astronomical Journal, 2003)
Stark widths (W) and shifts (d) of 5 prominent triply ionized oxygen (O IV) spectral lines in 3 multiplets have been measured in oxygen plasma at 42 000 K electron temperature using a linear, low-pressure, pulsed arc discharge as an optically thin plasma source. Obtained W and d values have been compared to available experimental and theoretical data. We found a good agreement among our experimental W and d values and theoretical expectations.